Strategic Synergy: Integrating Business Management with Computer Science for Competitive Advantage - Ahmad Nur Ihsan Purwanto; Athaya Abdan Hanif (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
In today's digital age, the integration of business management principles with computer science and technology has become increasingly vital for organizations seeking sustainable growth and competitive advantage. This study delves into the multifaceted relationship between business management and computer science, exploring integration strategies, challenges, and the resultant implications. The objective of this research is to comprehensively analyze the integration of business management and computer science, shedding light on effective strategies, potential challenges, and the overall impact on organizational performance and innovation. This study adopts a library research approach, encompassing a thorough review of existing literature, scholarly articles, case studies, and industry reports. Information is gathered from reputable databases such as PubMed, IEEE Xplore, ACM Digital Library, and Google Scholar. The collected data are analyzed qualitatively to identify patterns, trends, and insights into the integration of business management and computer science. The findings of this research highlight various integration strategies employed by organizations to leverage computer science and technology for enhancing business management practices. These strategies encompass the adoption of data analytics, artificial intelligence, machine learning, blockchain, and other emerging technologies to streamline operations, optimize decision-making processes, and gain competitive advantage. Moreover, the study identifies challenges associated with integration, including data security concerns, skills gap, resistance to change, and ethical implications. Despite these challenges, successful integration initiatives have demonstrated significant improvements in organizational efficiency, innovation capability, and market positioning